Development of models and methods to assess the efficacy of anti-cancer drugs targeted to the mitochondria - Potter, M (2014)
Background: Malignant transformation of cells is typically characterised by aerobic glycolysis, resulting in supressed mitochondrial function, a state that helps resistance to apoptosis. This characteristic has been widely accepted as a hallmark of cancer and has been shown to be of critical importance in tumour development. The bioenergetic differences between normal and malignant cells are being exploited to identify potential cancer specific therapeutics. Improved in-vitro models are required to aid the identification and assessment of candidate drugs. In this project, we investigated the bioenergetic phenotypes of a panel of adult and paediatric cancer cell lines and evaluated the potential of 3D models as a platform for testing drugs that target cancer metabolism. We also investigated a novel method to assess mitochondrial function that enables the quantification of the level of oxygenation within the cell. Results: The results presented in this thesis show that not all cancers display this aerobic glycolytic phenotype. We found that while some cell lines displayed the Warburg phenotype others displayed high levels of oxidative metabolism. These bioenergetic profiles need to be considered when deciding which anti-cancer drugs to use in a chemotherapeutic regime. If a bioenergetic pattern can be identified it may one day form the basis of a screening strategy for tumours. Dichloroacetate (DCA) is a small molecule PDK inhibitor that was investigated in this study. It was found to be relatively non-toxic to cells cultured in 2D but had improved toxicity when the cells were cultured in a 3D environment. Lastly, we evaluated a new oxygen sensing nanoprobe, Mito-Xpress Intra, and the results demonstrate its potential as a non-invasive means of measuring oxygen concentrations within the cell in real time as well as highlighting some striking differences between applied ambient and measured intracellular oxygen concentrations. Conclusion: The findings suggest that not all cancers display the characteristic glycolytic phenotype. They also highlight the importance of controlling oxygen and glucose levels when evaluating metabolism and when drug testing.